Beta - ThrombogloBulin And HA - Platelet Factor 4 In Multiple Myeloma, Hodgkin Disease And Malig - Nant Lymphoma - Effects Of Therapy - Klingemann, H G; Eqbrinq, R; Havemann, K (Thrombosis and Haemostasis, 1981)
Determination of platelet specific proteins Beta-Thromboglobulin ( β-TG) and High Affinity Platelet Factor 4 (PF 4) in plasma has been proved as useful marker for an enhanced release reaction in some diseases, mostly due to an in - creased platelet aggregation. To evaluate suit - able marker for a prethrombotic state in some myeloproliferative diseases ue investigated patients suffering from multiple myeloma, Hodgkin disease and malignant lymphoma. β- TG and PF 4 were measured in platelet poor plasma using RIA - kits (Amersham-Buchler / Abbott Labor.). In addition ue determined; platelet count, spontaneous and collagen induced platelet aggregation, the activity of AT III and of the clotting factors I, V, VIII, XIII and the concentration of FDP.RESULTS: Normal range was found to be 0-55 ng/ml forβ-TG and 0-12 ng/ml for PF 4. Both release proteins were increased in 17 out of 25 patients with myeloma, in 13 out of 15 patients with Hodgkin disease and in 10 out of 12 patients with malignant lymphoma. A correlation to the severity of the diseases were demonstrable. Chemotherapy caused a decrease of β -TG and PF 4 levels in some cases. However no correlation could be found between β- TG and PF 4 levels and in vitro tests of platelet aggregation. Further clotting assay provided evidence for an activation of clotting (like DIC) in a few patients. Other possibilities - like the release of the platelet specific proteins by immunocomplexes, prostaglandins or proteolytic enzymes from granulocytes must taken into account.